Cost analysis of nurse telephone consultation in out of hours primary care: evidence from a randomised controlled trial. Issue 7241 (15th April 2000) - Lattimer, Val; Sassi, Franco; George, Steve; Moore, Michael; Turnbull, Joanne; Mullee, Mark; Smith, Helen
Abstract: Objective: To undertake an economic evaluation of nurse telephone consultation using decision support software in comparison with usual general practice care provided by a general practice cooperative. Design: Cost analysis from an NHS perspective using stochastic data from a randomised controlled trial. Setting: General practice cooperative with 55 general practitioners serving 97 000 registered patients in Wiltshire, England. Subjects: All patients contacting the service, or about whom the service was contacted during the trial year (January 1997 to January 1998). Main outcome measures: Costs and savings to the NHS during the trial year. Results: The cost of providing nurse telephone consultation was £81 237 per annum. This, however, determined a £94 422 reduction of other costs for the NHS arising from reduced emergency admissions to hospital. Using point estimates for savings, the cost analysis, combined with the analysis of outcomes, showed a dominance situation for the intervention over general practice cooperative care alone. If a larger improvement in outcomes is assumed (upper 95% confidence limit) NHS savings increase to £123 824 per annum. Savings of only £3728 would, however, arise in a scenario where lower 95% confidence limits for outcome differences were observed. To break even, the intervention would have needed to save 138 emergency hospital admissions per year, around 90% of the effect achieved in the trial. Additional savings of £16 928 for general practice arose from reduced travel to visit patients at home and fewer surgery appointments within three days of a call. Conclusions: Nurse telephone consultation in out of hours primary care may reduce NHS costs in the long term by reducing demand for emergency admission to hospital. General practitioners currently bear most of the cost of nurse telephone consultation and benefit least from the savings associated with it. This indicates that the service produces benefits in terms of service quality, which are beyond the reach of this cost analysis.